The Aplication of Max-Plus Algebra to Determine The Optimal Time of Ikat Kupang Woven Production - Lusiana Prastiwi; Yuni Listiana (LPPM Institut Teknologi Sepuluh Nopember, 2017)
The problem of scheduling is a problem that becomes part of project management that aims to plan the implementation of activities in a project in a structured manner with a clear time limit. Kupang ikat woven is an Indonesian handicraft that the process of making it through the stages of structured activities with a long time limit. Thus, in this study we intend to estimate the optimal time required to manufacture the Kupang ikat woven by applying the Max-Plus algebra method. In this case, the linkages between activities within a project can be transformed into a matrix form which can be analyzed using Max-Plus algebra method. This matrix will be applied in the calculation to get the solution needed in project scheduling, in this case is the optimum time required of making Kupang ikat woven.